IMPLEMENTASI PEMBELAJARAN IPA MODEL PBL ISLAMI BERBANTUAN SELAWAT SAINS DI SEKOLAH DASAR BERBASIS PESANTREN - Yuniar Fahmi Lathif; Dwi Irsyad Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of Natural Science (IPA) instruction using an Islamic Problem-Based Learning (PBL) model supported by science salawat in an Islamic boarding school-based elementary school. A descriptive qualitative research method was employed. Data collection involved classroom observations, in-depth interviews with teachers and students, and documentation of the learning process. The results indicate that the implementation of Islamic PBL supported by science salawat effectively enhanced students' ecological understanding and critical thinking skills regarding environmental problem-solving. The integration of Islamic values ​​was realized by framing pollution issues around the boarding school within the context of contemplation of Quranic verses prohibiting the destruction of the earth. Meanwhile, science salawat served as both an interactive medium and a means of spiritual reflection, reinforcing students' retention of scientific concepts in a meaningful way. The primary challenge encountered was time constraints in completing all stages of the Islamic PBL model amidst the school's rigorous schedule of boarding activities. The study concludes that the Islamic PBL model supported by science salawat successfully harmonizes academic achievement in science with the internalization of religious values ​​among students from an early age.